Peningkatan Pengetahuan Lansia Melalui Edukasi Hipertensi: Sebuah Upaya Pencegahan Kejadian Hipertensi pada Lansia Di Desa Jeti, Kecamatan Baki: Increasing Elderly Knowledge Through Hypertension Education: An Effort to Prevent Hypertension Incidents in the Elderly in Jeti Village, Baki District - Irawan, Ady; Widiastuti, Agung; Shinta Dewi, Febrianti; Pradana Putri, Anggie (Chakra Brahmanda Lentera Institute, 2024)
Physiological changes in the elderly make them vulnerable to chronic diseases. The elderly are a vulnerable population to hypertension cases, as one of the chronic diseases in Indonesia. Efforts are needed to provide health services that can be provided by nurses through a community approach with the parties involved, such as the elderly. This community service is carried out through health education and counseling on hypertension management followed by knowledge evaluation. These efforts can be realized by holding counseling activities on hypertension. This community service activity involved 30 elderly people in Jetis Village, Sukoharjo, with 53% experiencing high hypertension. The activity took place from December 15-21, 2023, including preparation, intervention, and evaluation. The intervention was in the form of health education about hypertension and blood sugar for 2 x 60 minutes, with flip sheet media and group discussion. The evaluation was carried out by t-test on SPSS 22.0 to analyze the increase in knowledge. The measuring tools used were a glucometer, sphygmomanometer, and questionnaire (Cronbach's alpha = 0.80), with normal blood sugar values of 80-100 mg/dL and blood pressure of 130-140 mmHg (systolic) and 80-90 mmHg (diastolic). The results of the counseling activities on hypertension showed that the age of the participating people was mostly 50-75 years old with a total of 30 people (57%), the gender was mostly female, namely 25 people (83%) while 5 men (17%). A total of 16 people (53%) had high hypertension and normal hypertension (47%). A total of 18 people (39%) had good knowledge before counseling and 28 people (61%) had good knowledge after counseling. Health education and counseling on hypertension management effectively increased knowledge among older adults with hypertension who participated in this study. Providing health education is recommended to improve hypertension management.